ANALISIS EFISIENSI USAHATANI STROBERI (Fragaria x ananassa) (Studi Kasus : Desa Dolat Rakyat Kecamatan Dolat Rakyat Kabupaten Karo) - Asmina Herawaty Sinaga; Firman Laia (Jurnal Darma Agung, 2020)
The purpose of this study is (1) to analyze the amount of strawberry ushatani income, starting from production, selling price, revenue to net income, (2) analyzing the level of optimization of the use of inputs on strawberry farming, (3) knowing the feasibility of strawberry ushatani, is it worth the effort or not. The amount of income of a sample farmer is influenced by age, farming experience and the number of production factors used. The everage strawberry production in the study area is 1,077,915 kg with an average land area of 0,23 H. The income and income of sample farmers also have an importent effect on the selling price of production, where the everage selling price of farmers in the study area is quite large, namely Rp25,000 / kg. The everage acceptance of sample farmers in the study area is Rp26,947,875 with an average production cost of Rp21,292,126 so that it receives an average net income of Rp5,655,749/year. And this very low when compared to UMK Karo of Rp2,619,234.41. Strawberry farmers in the study area mostly have a fairly low aducation of 9 years, therefore farmers have minimal knowledge in cultivation and marketing techniques and also the lack of farmers in terns of farm management that does not take into account the supporting factors of farming and use more than one (1), sucs as pesatisida with the same function so that it will increase production costs, as well as low access to farmers’s capabilites in government and banking policies. Keywords : Optomization, Strawberry.